2021
DOI: 10.3389/fcvm.2021.644264
|View full text |Cite
|
Sign up to set email alerts
|

Rate of Progression of Aortic Stenosis in Patients With Cancer

Abstract: Patients with cancer and aortic stenosis (AS) are exposed to several factors that could accelerate the progression of AS. This study aimed to determine the cumulative incidence of AS progression and associated factors in these patients. This retrospective cohort study included patients with cancer, mild or moderate AS and at least two echocardiograms 6 months apart between 1996 and 2016 at MD Anderson Cancer Center. AS progression was defined by an increase in mean gradient of 20 mmHg or peak velocity of 2 m/s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Moreover, chest radiation and cardiotoxic drugs (i.e., anthracyclines) have been noted to produce de novo AS via valve leaflet thickening, fibrosis, retraction, and calcification [ 15 ], but, at the present, the impact that they may have on AS progression has not been studied. Bravo-Jaimes et al have found that patients with mild or moderate AS and cancer are more likely to die before having AS progression, which is, in turn, associated with CAD and prevalent cyclophosphamide use [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, chest radiation and cardiotoxic drugs (i.e., anthracyclines) have been noted to produce de novo AS via valve leaflet thickening, fibrosis, retraction, and calcification [ 15 ], but, at the present, the impact that they may have on AS progression has not been studied. Bravo-Jaimes et al have found that patients with mild or moderate AS and cancer are more likely to die before having AS progression, which is, in turn, associated with CAD and prevalent cyclophosphamide use [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…They deform into an elliptical shape following motion [6]. It is generally recognized that irregular intravascular growth causes stenosis to form at different points in the arterial system, reducing the lumen and obstructing blood flow [7]. High risk of death is experienced in a patient with cancer and aortic stenosis [7].…”
Section: Introductionmentioning
confidence: 99%
“…It is generally recognized that irregular intravascular growth causes stenosis to form at different points in the arterial system, reducing the lumen and obstructing blood flow [7]. High risk of death is experienced in a patient with cancer and aortic stenosis [7]. It has been suggested that the mechanical factors have significant role to determine where atherosclerosis occurs, low mean and oscillatory fluid wall shear stresses are also estimated to be responsible for the stenosis [8,9].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations